2016
DOI: 10.1186/s12913-016-1915-3
|View full text |Cite
|
Sign up to set email alerts
|

The economic impact of mental healthcare consumption before and after stroke in a cohort of stroke patients in the Netherlands: a record linkage study

Abstract: BackgroundPost-stroke healthcare consumption is strongly associated with a mental health diagnosis. This study aimed to identify stroke patients who utilised mental healthcare facilities, explored their mental healthcare consumption pre-stroke and post-stroke, and examined possible predictors of costs incurred by mental healthcare consumption post-stroke.MethodsThree databases were integrated, namely the Maastricht University Medical Centre (MUMC) Medical Administration, the Stroke Registry from the Department… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…ABI can be associated with significant and chronic impairments across multiple areas of functioning including physical, cognitive, emotional, behavioral and social domains (Milders et al, 2003;Barman et al, 2016;de Freitas Cardoso et al, 2019;Kane et al, 2019). Critically, the psychological consequences of ABI are generally hidden and are associated with poor involvement in rehabilitation, hospital readmission, long-term disability, limited social activity, reduced ability to manage physical conditions, increased health service usage, suicide and a general increase in risk for mortality (Gillen et al, 2001;Naylor et al, 2012;Ayerbe et al, 2013;van Eeden et al, 2016). People affected by ABI -as with other chronic conditions -have little access to psycho-social interventions to address ongoing holistic needs: almost three-quarters of people living with ABI feel that their psychological needs are not met (McKevitt et al, 2011;Oyesanya, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…ABI can be associated with significant and chronic impairments across multiple areas of functioning including physical, cognitive, emotional, behavioral and social domains (Milders et al, 2003;Barman et al, 2016;de Freitas Cardoso et al, 2019;Kane et al, 2019). Critically, the psychological consequences of ABI are generally hidden and are associated with poor involvement in rehabilitation, hospital readmission, long-term disability, limited social activity, reduced ability to manage physical conditions, increased health service usage, suicide and a general increase in risk for mortality (Gillen et al, 2001;Naylor et al, 2012;Ayerbe et al, 2013;van Eeden et al, 2016). People affected by ABI -as with other chronic conditions -have little access to psycho-social interventions to address ongoing holistic needs: almost three-quarters of people living with ABI feel that their psychological needs are not met (McKevitt et al, 2011;Oyesanya, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Stroke Association () found that 73% of stroke survivors lacked confidence, 56% felt people treated them differently, and 55% felt unable to care for their families as before. Stroke‐related comorbidities are associated with reduced quality of life (Bays, ; Godwin, Ostwald, Cron, & Wasserman, ; Sturm et al ., ), increased mortality (Ayerbe et al ., ), increased health care utilization (Appleby, Thompson, & Galea, ; Ghose, Williams, & Swindle, ; van Eeden et al ., ), and reduced functional recovery (Gillen, Tennen, McKee, & Gernert‐Dott, ).…”
Section: Introductionmentioning
confidence: 99%
“…Stroke is the leading cause of disability [1] and is a major cause of morbidity [2], leading to high economic burden worldwide. About 30% patients die directly due to the disease each year, and similar percentage of sufferers are functionally disabled [2,3].…”
Section: Introductionmentioning
confidence: 99%